2016
DOI: 10.1002/ajcp.12112
|View full text |Cite
|
Sign up to set email alerts
|

Finding Home: A Qualitative Approach to Understanding Adolescent Mothers’ Housing Instability

Abstract: Many low-income Latina adolescent mothers face instability in their housing circumstances, which has implications for their long-term prospects and that of their children. This study used longitudinal, ethnographic data from Welfare, Children, and Families: A Three City Study to explore experiences of low-income, Latina adolescent mothers (N = 15) with unstable housing who primarily rely on their families or the families of their significant others for housing support. Results of analysis employing grounded th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Linked administrative records provide population‐level and prospective data to explore the intersection between child welfare involvement and homelessness (Putnam‐Hornstein, Lery, Hoonhout, & Curry, ; Shah et al., ). Ethnographic data collection embedded within a representative and longitudinal survey of low‐income families illuminates how young Latina mothers navigate housing instability (Elliott, Shuey, Zaika, Mims & Leventhal, ). Collectively, the studies show the prevalence of homelessness among vulnerable youth and identify key risk and protective processes.…”
Section: Summaries Of Contributions In Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Linked administrative records provide population‐level and prospective data to explore the intersection between child welfare involvement and homelessness (Putnam‐Hornstein, Lery, Hoonhout, & Curry, ; Shah et al., ). Ethnographic data collection embedded within a representative and longitudinal survey of low‐income families illuminates how young Latina mothers navigate housing instability (Elliott, Shuey, Zaika, Mims & Leventhal, ). Collectively, the studies show the prevalence of homelessness among vulnerable youth and identify key risk and protective processes.…”
Section: Summaries Of Contributions In Contextmentioning
confidence: 99%
“…Elliott et al. () conducted a qualitative study of the experiences of 15 Latina adolescent mothers. Grounded theory and narrative analyses shed light on two types of housing instability: “horizontal” moves across family homes and “vertical” moves between living with family and independent living.…”
Section: Summaries Of Contributions In Contextmentioning
confidence: 99%
“…Few studies have explored family systems of sexuality communication, but research stemming from family systems theory [ 18 ] has identified the importance of investigating the larger family system to understand children’s development, rather than assessing parent–child relationships in isolation [ 19 ]. Research suggests that how family systems interact can impact youth development [ 20 , 21 ]. For example, research has explored how sibling relationships interact with parent–child relationships, e.g., [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adolescence is a period of chaos and a time when someone faces many problems, challenges, and conflicts in the search for identity (Elliott et al, 2017). This period is a transition from childhood to adulthood, a period when someone who departs to seek identity becomes an adult (Elliott et al, 2017;Houltberg et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Adolescence is a period of chaos and a time when someone faces many problems, challenges, and conflicts in the search for identity (Elliott et al, 2017). This period is a transition from childhood to adulthood, a period when someone who departs to seek identity becomes an adult (Elliott et al, 2017;Houltberg et al, 2016). They tend to spend more time with peer groups rather than being at home, and if social interactions are positive, it will undoubtedly be beneficial for adolescent development (Tompsett et al, 2016).…”
Section: Introductionmentioning
confidence: 99%